Antiepileptic and Antidepressive Polypharmacy in Patients with Multiple Sclerosis. (29th June 2015) - Beiske, Georg Anton Giæver; Holmøy, Trygve; Beiske, Antonie Giæver; Johannessen, Svein I.; Johannessen Landmark, Cecilie
Abstract : Objective . Patients with multiple sclerosis (MS) are often suffering from neuropathic pain. Antiepileptic drugs (AEDs) and tricyclic antidepressants (TCAs) are commonly used and are susceptible to be involved in drug interactions. The aim of this retrospective study was to investigate the prevalence of use of antiepileptic and antidepressive drugs in MS patients and to discuss the theoretical potential for interactions. Methods . Review of the medical records from all patients treated at a dedicated MS rehabilitation centre in Norway between 2009 and 2012. Results . In total 1090 patients attended a rehabilitation stay during the study period. Of these, 342 (31%; 249 females) with mean age of 53 (±10) years and EDSS 4.8 (±1.7) used at least one AED (gabapentin 12.7%, pregabalin 7.7%, clonazepam 7.8%, and carbamazepine 2.6%) or amitriptyline (9.7%). Polypharmacy was widespread (mean 5.4 drugs) with 60% using additional CNS-active drugs with a propensity to be involved in interactions. Age, gender, and EDSS scores did not differ significantly between those using and not using AED/amitriptyline. Conclusion . One-third of MS patients attending a rehabilitation stay receive AED/amitriptyline treatment. The high prevalence of polypharmacy and use of CNS-active drugs calls for awareness of especially pharmacodynamic interactions and possible excessive adverse effects.